Aluminum-silicon carbide composites for enhanced physio- mechanical properties - Debnath, Sujan; Chee, Won Yeo; Rahman, Muhammad Ekhlasur; Reddy, Moola Mohan; Maleque, Md. Abdul; Ali, Mohammad Yeakub (Trans Tech Publications, Switzerland, 2012)
Stir casting method is used in the production of SiC reinforced-aluminium metal matrix composite (AMMC) to enhance the properties of base metal. Different weight fraction of Silicon carbide, SiC (5 wt%, 10 wt% and 15 wt %) particulate-reinforced AMMCs are fabricated and characterizations of physical and mechanical properties of the materials are performed based on the experimental. The microstructure of the fabricated composite material are studied and analyzed. The results indicate that the mechanical properties of the composite, including yield strength, tensile strength and hardness are enhanced by the increment of the weight fraction of reinforcing phase. Nevertheless, the elongation and fracture toughness of the composite decreased as the reinforcing phase increased. This is mainly due to the brittleness of the SiC particles which act as micro void initiator.